Condensed tannins increase nitrogen recovery by trees following insect defoliation. Issue 2 (7th May 2015) - Madritch, Michael D.; Lindroth, Richard L.
Summary While the importance of plant secondary metabolites to belowground functioning is gaining recognition, the perception remains that secondary metabolites are produced for herbivore defense, whereas their belowground impacts are ecological by‐products, or 'afterlife' effects. However, plants invest a significant amount of resources into production of secondary metabolites that have minimal effects on herbivore resistance (e.g. condensed tannins and insect herbivores). We show that genetically mediated variation in condensed tannin concentration is correlated with plant nitrogen recovery following a severe defoliation event. We used single‐tree mesocosms labeled with 15N to track nitrogen through both the frass and litter cycling pathways. High concentrations of leaf tannins in Populus tremuloides were correlated with 15N recovery from frass within the same growing season and in the following growing season. Likewise, leaf tannin concentrations were also correlated with 15N recovery from the litter of defoliated trees in the growing season following the defoliation event. Conversely, tannins were not well correlated with nitrogen uptake under conditions of nominal herbivory. Our results suggest that tannins may confer benefits in response to herbivore pressure through conserved belowground nitrogen cycling, rather than via defensive properties. Consequently, tannins may be considered as chemical mediators of tolerance rather than resistance.